A novel Tenebrio molitor cadherin is a functional receptor for Bacillus thuringiensis cry3aa toxin - Fabrick, Jeff; Oppert, Chris; Lorenzen, Marce D.; Morris, Kaley; Oppert, Brenda; Jurat-Fuentes, Juan Luis (My University, 2009)
Cry toxins produced by the bacterium Bacillus thuringiensis (Bt) are effective biological insecticides. Cadherin-like proteins have been reported as functional Cry1A toxin receptors in Lepidoptera. Here we present data that demonstrate a coleopteran cadherin is a functional Cry3Aa toxin receptor. The Cry3Aa receptor cadherin was cloned from Tenebrio molitor larval midgut mRNA, and the predicted protein, TmCad1, has domain structure and a putative toxin binding region similar to those in lepidopteran cadherin Bt receptors. A peptide containing the putative toxin binding region from TmCad1 (rTmCad1p) bound specifically to Cry3Aa and promoted the formation of Cry3Aa toxin oligomers, proposed to be mediators of toxicity in lepidopterans. Injection of TmCad1-specific dsRNA into T. molitor larvae resulted in knockdown of TmCad1 transcript and conferred resistance to Cry3Aa toxicity. These data demonstrate the functional role of TmCad1 as a Cry3Aa receptor in T. molitor and reveal similarities between the mode of action of Cry toxins in Lepidoptera and Coleoptera.
Citation: Fabrick, J., & Oppert, C. (2009). A Novel Tenebrio molitor Cadherin Is a Functional Receptor for Bacillus thuringiensis Cry3Aa Toxin. 284(27), 18401-18410. https://doi.org/10.1074/jbc.M109.001651
Keywords: Bacillus thuringiensis; Cry3Aa; Coleoptera; Tenebrio molitor; Toxin mode of action; Insect cadherin